INVESTIGATION OF FAST NEURON ATTENUATION COEFFICIENTS FOR SOME IRAQI BUILDING MATERIALS - Mkhaiber, Ahmed; Al-Bayati, Auday; Fadhil, Itab (Malaysian Journal of Science, 2022)
This research aims to improve the radiation shielding properties of polymer-based materials by mixing PVC with locally available building materials. Specifically, two key parameters of fast neutron attenuation (removal cross-section and half-value layer) were studied for composite materials comprising PVC reinforced with common building materials (cement, sand, gypsum and marble) in different proportions (10%, 30% and 50% by weight). To assess their effectiveness as protection against fast neutrons, the macroscopic neutron cross-section was calculated for each composite. Results show that neutron cross-section values are significantly affected by the reinforcement ratios, and that the composite material PVC + 50% gypsum is an effective shield against fast neutrons.